2020
DOI: 10.1021/acs.estlett.0c00291
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Charge Weakly Affects Ion Transport in Reverse Osmosis

Abstract: Polyamide reverse osmosis (RO) membranes have been a "golden standard" in water desalination, with an aromatic polyamide layer providing an excellent balance between salt rejection and water permeability. Yet, there still are gaps in understanding the salt transport in RO, closely related to the nature and formation of membrane charge and its effect on ion permeation. We report here a systematic investigation that examines the correlation between the nominal membrane charge, determined by ion-binding methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…In this case, R 2 -NH 2 + densities would be representative of the total R 2 -NH content (i.e., surface and interior). The roughly constant value for Br − uptake below pH 7 also suggests that the counterion probe is associating with ionized amine groups rather than being cosorbed alongside protons, as has been recently proposed for fully aromatic polyamides (33)(34)(35). If proton uptake was the predominant means by which Br − was associated into the membrane, one would instead expect an exponential increase in Br − uptake as pH decreases.…”
Section: Areal R 2 -Nhmentioning
confidence: 60%
“…In this case, R 2 -NH 2 + densities would be representative of the total R 2 -NH content (i.e., surface and interior). The roughly constant value for Br − uptake below pH 7 also suggests that the counterion probe is associating with ionized amine groups rather than being cosorbed alongside protons, as has been recently proposed for fully aromatic polyamides (33)(34)(35). If proton uptake was the predominant means by which Br − was associated into the membrane, one would instead expect an exponential increase in Br − uptake as pH decreases.…”
Section: Areal R 2 -Nhmentioning
confidence: 60%
“…One interesting aspect for future research is to explore the use of specific chemistry of interlayer materials for improving the selectivity against target contaminants. 98,99,247 Furthermore, advanced membrane characterization techniques (e.g., QCM-D, 57,121 Rutherford backscattering spectrometry, 284,285 electrochemical impedance spectroscopy, 286,287 tron annihilation lifetime spectroscopy, 288,289 3D TEM tomography, 290,291 and so on. 146,154,292,293 ) are needed.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…on both water permeance and selectivity. One interesting aspect for future research is to explore the use of specific chemistry of interlayer materials for improving the selectivity against target contaminants. ,, Furthermore, advanced membrane characterization techniques (e.g., QCM-D, , Rutherford backscattering spectrometry, , electrochemical impedance spectroscopy, , positron annihilation lifetime spectroscopy, , 3D TEM tomography, , and so on. ,,, ) are needed. Such advanced characterization can provide better understanding of the effect of interlayers on the physiochemical properties of polyamide layers, particularly with respect to the orientation/pattern of nanofillers, their interactions with the rejection layer and substrate, their effect on the transport behavior and the overall membrane integrity, ,,, which are critical issues for many membrane applications.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Another study revealed that sodium ion diffusion is reduced when the ions interact with 12-crown-4 ligands . Ion–functional group association is expected to have a lessened effect on diffusion as the charge of the functional group becomes saturated with ions, shielding the charge of functional groups from other ions …”
Section: Transport and Interfacial Interactionsmentioning
confidence: 99%
“…66 Ion−functional group association is expected to have a lessened effect on diffusion as the charge of the functional group becomes saturated with ions, shielding the charge of functional groups from other ions. 67 MD simulations 24,25 revealed that water partitioning into reverse osmosis polymeric membranes is energetically favorable with a partition coefficient of 0.3. Hydrodynamic resistance that water experiences at the entrance only accounts for 4−7% of the total resistance to water flow for a simulated model of a polyamide membrane.…”
Section: ■ Transport and Interfacial Interactionsmentioning
confidence: 99%